Stomach Carcinoma Presenting with a Synchronous Liver Cancer: A Case Report and Literature Review - Yong Wang; Xiao-ting Wu (Case Reports in Gastrointestinal Medicine)
Multiple primary malignant neoplasms are two or more malignancies in an individual without any relationship between the tumors. Multiple primary malignancies are relatively rare but have increased in recent decades. Two cancers are commonly observed among those with multiple primary malignancies, but two malignancies of stomach and liver are relatively rare to be reported. Mechanisms of the tumors were unclear; we described a patient who had stomach carcinoma presenting with a synchronous liver cancer and investigated his family history; we suggest that family history may be a key risk factor and early detection for additional primary malignancies should be needed for patients who had specific cancer history in their pedigree. Early diagnosis may be the key risk factor affecting prognosis.